Middle ear choristoma presenting as cholesteatoma with conductive hearing loss. Issue 4 (27th April 2019) - Purnell, Phillip R; Interval, Erik; Williams, H James; Cassis, Adam
Abstract: A 6-year-old male was seen for evaluation of middle ear polyp with associated hearing loss and otorrhea. CT scan revealed canal polyp with a stalk extending to the middle ear with malformation of the malleus and incus. The patient underwent exploratory tympanotomy which revealed a fistula from the bony-cartilaginous junction connecting to a middle ear mass which had eroded the incus. Intraoperative pathology suggested columnar epithelium without cholesteatoma or muscle. Final pathologic diagnosis reported dense fibrous tissue as well as ectopic salivary gland tissue, consistent with salivary gland choristoma. After removal of the mass, a partial prosthesis was successfully placed. Middle ear salivary gland choristoma is a rare entity. It can be confused clinically with cholesteatoma and is usually diagnosed on pathology. This diagnosis is often associated with other external, middle, and inner ear abnormalities.